2012
DOI: 10.3109/0886022x.2012.731970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Abbreviated Modification of Diet in Renal Disease Formula (aMDRD) and the Cockroft–Gault Adjusted for Body Surface (aCG) Equations in Stable Renal Transplant Patients and Living Kidney Donors

Abstract: The performance of abbreviated Modification of Diet in Renal Disease formula (aMDRD) and the Cockroft-Gault adjusted for body surface (aCG) equations as compared with measured 125 I-iothalamate glomerular filtration rate was analyzed in patients with stable renal transplantation (RTx) and in potential living kidney donors (LKD). One hundred and thirty-one patients had RTx and 150 were LKD. The paired t-test showed that the estimated glomerular filtration rate (GFR) values through the aMDRD and the corrected CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Proteinuria is a well-known marker of disease progression. [17] In this meta-analysis, the estimated rate of ESRD in donors was approximately 1.0%, higher than 0.1% to 0.5% reported in previous studies. [5,18,19] In fact, a recent study has shown similar findings of increased risk of ESRD in LKDs.…”
Section: Discussionmentioning
confidence: 57%
“…Proteinuria is a well-known marker of disease progression. [17] In this meta-analysis, the estimated rate of ESRD in donors was approximately 1.0%, higher than 0.1% to 0.5% reported in previous studies. [5,18,19] In fact, a recent study has shown similar findings of increased risk of ESRD in LKDs.…”
Section: Discussionmentioning
confidence: 57%
“…The estimated glomerular filtration rate (eGFR) was calculated using the abbreviated modification of diet in renal disease (MDRD) formula. 19 The time-weighted lipid and glucose profiles were also calculated by the products of the sums of two consecutive measurements and the time interval, then divided by the total time interval, as suggested previously. 20…”
Section: Methodsmentioning
confidence: 99%
“…The estimated glomerular filtration rate (eGFR) was calculated using the abbreviated modification of diet in renal disease (MDRD) formula. [14] Furthermore, the time-weighted lipid and glucose profiles after drug initiation were also calculated by the products of the sums of two consecutive measurements and the time interval, then divided by the total time interval, as suggested previously. [15]…”
Section: Methodsmentioning
confidence: 99%